The History and Cultural Heritage of Chinese Calligraphy, Printing and Library Work - Allen, Susan M. (IFLA Publications, 2010)
In China the tradition of a book society is longer than anywhere else in the world. Chinese paper making, calligraphy and woodblock printing date from very early ages, but have for a very long time remained almost unknown to the Western world. At the IFLA satellite meeting ?Chinese Written and Printed Cultural Heritage and Library Work? in Hangzhou in 2006 the richness of present day book historical research and library activities in China has been presented by more than sixty papers. This fine selection reflects the width and depth of this extremely important and immense Chinese heritage.